Future Prospects of Direct Air Capture Technologies: Insights From an Expert Elicitation Survey - Shayegh, Soheil; Bosetti, Valentina; Tavoni, Massimo (Frontiers in Climate, 2021)
Direct air capture (DAC) technologies are promising but speculative. Their prospect as an affordable negative emissions option that can be deployed in large scale is particularly uncertain. Here, we report the results of an expert elicitation about the evolution of techno-economic factors characterizing DAC over time and across climate scenarios. This is the first study reporting technical experts' judgments on future costs under different scenarios, for two time periods, for two policy options, and for two different DAC technologies. Experts project CO2 removal costs to decline significantly over time but to remain expensive (median by mid-century: around 200 USD/tCO2). Nonetheless, the role of direct air capture in a 2°C policy scenario is expected to be significant (by 2050: 1.7 [0.2, 5.9] GtCO2)1. Projections align with scenarios from integrated assessment model (IAM) studies. Agreement across experts regarding which type of DAC technology might prevail is low. Energy usage and policy support are considered the most critical factors driving these technologies' future growth.